2009
DOI: 10.1007/s00221-009-2096-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ensuing actions in children and adolescents with autism spectrum disorders

Abstract: This study investigated the ability to predict others' action in a group of children and adolescents with autism spectrum disorders (ASD) (n = 18). Their performance was compared with a group of children with mental retardation (n = 13) and a group of children with typical development (n = 19). Participants were presented with short incomplete videotaped movies showing an actor executing familiar and non-familiar actions. When asked to predict the outcome, participants with ASD produced fewer correct responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Happé 1997). Although an impaired ability to utilise action kinematics and object knowledge to predict the most likely end-point of an action sequence has been demonstrated in children and adolescents with low functioning autism (Zalla et al 2010), it is as yet unknown to what extent problems in the involuntary processing of social cues in ASD may give rise to problems in anticipating other's actions.…”
Section: Social Cue Processing In Autism Spectrum Disordermentioning
confidence: 99%
“…Happé 1997). Although an impaired ability to utilise action kinematics and object knowledge to predict the most likely end-point of an action sequence has been demonstrated in children and adolescents with low functioning autism (Zalla et al 2010), it is as yet unknown to what extent problems in the involuntary processing of social cues in ASD may give rise to problems in anticipating other's actions.…”
Section: Social Cue Processing In Autism Spectrum Disordermentioning
confidence: 99%
“…Difficulties in understanding and predicting others’ actions, as well as difficulties in theory of mind and social-cognitive skills, are frequently documented in children with autism (Baron-Cohen, 1995; Boria et al, 2009; Cattaneo et al, 2007; Zalla, Labruyère, Clément, & Georgieff, 2010), a neurodevelopmental disorder characterized by multiple deficits in the areas of social communication and reciprocity and by behavioral rigidity (Kanner, 1943; Rutter, 1978; Volkmar, Lord, Bailey, Schultz, & Klin, 2004). Social-cognitive studies have focused for many years on understanding these deficits in autism.…”
mentioning
confidence: 99%
“…This is ironic given that actions are inherently dynamic as they unfold with time. Only a few studies have acknowledged this dynamic aspect by using action video clips, rather than action photographs, as stimulus materials (e.g., Hamilton & Grafton, 2008;Spunt et al, 2011;Zalla, Labruyère, Clément, & Georgieff, 2010). One reason for this restriction is very likely the fact that preparation and production of video clips is time consuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that an action's familiarity influences perceptual processing, memory performance, imitation, and outcome prediction (e.g., CalvoMerino, Ehrenberg, Leung, & Haggard, 2010;Knopf, 1991;Wang, Fu, Aschersleben, & Zimmer, 2012;Zalla et al, 2010). The familiarity status of actions and tools can also modulate brain activation patterns (e.g., Calvo-Merino, Grèzes, Glaser, Passingham, & Haggard, 2006;Rumiati et al, 2005;Vingerhoets, Acke, Vandemaele, & Achten, 2009).…”
Section: Introductionmentioning
confidence: 99%